The role of adiponectin in regulation of metabolism in dairy cows. - Kalamaras, Konstantinos (2012)
Body condition score has been considered an indirect measure of nutritional status and nutrition has been demonstrated to interact with reproduction. Adiponectin and leptin, because of its insulin sensitising actions and their association with body condition could be potential regulators of metabolism during the transition from pregnancy to lactation. The work described in this PhD project was designed to investigate the role of metabolic, body condition, and dietary factors in regulation of productive and reproductive performance in dairy cows, with particular regard to glucose homeostasis and adipokines. A special focus was directed to circulating adiponectin and its association with metabolic and hormonal status, and reproduction. Interestingly, adiponectin was found to be present in bovine milk at concentrations similar those of plasma. Body condition score, GH, insulin, leptin, and adiponectin showed a potential to modulate glucose homeostasis and reproductive output. Results from this study demonstrated a negative effect of long-term moderately elevated insulin concentration on reproductive performance. Additionally, BCS at calving and ΔBCS are determinant factors influencing postpartum reproductive recovery and they should be basic components of farming monitoring schemes. Although further investigation is needed to address the proposed negative relationship between adiponectin and GH, and to identify other dietary factors that may modulate circulating adiponectin, data from this study support regulatory roles of adiponectin in metabolism and reproduction. Moreover, adiponectin holds great promise to serve as a putative target molecule that integrates metabolism, reproduction and feeding behaviour. More importantly, hypoadiponectinemia could be another alternative mechanism that contributes to poor fertility in dairy cows. The incorporation of this new knowledge into the development of better nutritional strategies is a key point that is being considered to improve the welfare, and reproductive and productive performance in dairy cows.